The Psychometric Properties of the Meaning in Life Questionnaire (MLQ) in Patients with Life-Threatening Illnesses - Maede Naghiyaee; Bahman Bahmani; Ali Asgari (The Scientific World Journal)
Background. Meaning in life is one of the psychological domains that is most severely affected in patients with life-threatening illnesses. The importance of meaning-making mandates the development of reliable tools to assess this construct. Steger’s Meaning in Life Questionnaire (MLQ) is one of the most valid and reliable instruments that determines the search for and presence of meaning in life. The present study was conducted to provide psychometric data on the MLQ in a sample of patients with life-threatening illnesses. Methods. The MLQ was completed by 301 patients (aged 20–80 years) diagnosed with life-threatening illnesses (cancer and multiple sclerosis) and referred to hospitals. Confirmatory factor analysis and Pearson’s correlation test were used to determine the construct validity of the questionnaire. Results. The confirmatory factor analysis supported the original two-factor model of the MLQ, comprised of the presence of meaning (five items) and search for meaning (five items). The responses to the MLQ did not differ by sociodemographic factors. Most importantly, contrary to previous findings, the correlation between the two subscales, i.e., search for meaning and presence of meaning, was significant and positive. Conclusion. The results showed that the MLQ is a valid and reliable measure for assessing meaning in life that can be applied in research on meaning in life among other patient populations.